Coating and drying processes for functional films in polymer solar cells - from laboratory to pilot scale - Wengeler, Lukas (KIT Scientific Publishing, 2014)
Polymer solar cells can be produced by a continuous low cost coating and drying process. This work details a specialized experimental set-up to enable large scale roll to roll processing. Material properties such as surface energy, surface tension, and viscosity are presented and modelled. The impact of coating method, as well as process parameters (e.g. coating speed, shear rate, solvent composition) on process stability and film properties, is discussed.